Pengembangan E-Modul Penataan Sanggul Ciwidey Berbasis Canva pada Mahasiswa D4 Kosmetik dan Perawatan Kecantikan - Raysha Adhiasha; Sri Irtawidjajanti; Dwi Atmanto (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aimed to develop and evaluate the feasibility and practicality of a Canva-based electronic module for Ciwidey traditional hair styling in the Indonesian Bridal course. The study employed a Research and Development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The research was conducted from May to July 2026 at Universitas Negeri Jakarta and involved students of the 2022 D4 Cosmetics and Beauty Care cohort who had completed the Indonesian Bridal course. Data were collected using five-point Likert-scale questionnaires administered to a material expert and a media expert. Product practicality was assessed through a one-to-one trial involving five students and a small-group trial involving 40 students. The developed e-module contained syst ematically organized material, illustrations, practical documentation, instructional videos, navigation features, and formative quizzes. After revision, the material expert validation score increased from 75.56% to 93.33%, while the media expert validation score increased from 65.88% to 83.53%; both were classified as highly feasible. The one-to-one practicality test obtained a score of 92.20%, and the small-group test obtained 90.88%, both classified as highly practical. These findings indicate that the Canva-based Ciwidey hair styling e-module is feasible and practical for use as a supplementary learning medium and an independent learning resource. However, its effectiveness in improving learning outcomes has not yet been examined.